THE CONCEPT OF PROPERTY OWNERSHIP ACCORDING TO ABU AHRA TO REALIZE ECONOMIC BALANCE - Azhari, Muhammad Vicki; Wahab, Abdul (Universitas Muhammadiyah Surabaya, 2024)
Islamic law guarantees humanity's benefit in all matters, including property ownership and management of natural resources. Property rights are the rights of every individual that must be respected and must not be violated. However, for the common good, some things are considered common needs and must be managed to benefit humanity as a whole. This writing is literature research using a qualitative descriptive method, examining the theory of thought and the concept of ownership according to Imam Abu Zahra in muamalah fiqh. The research results show that in Islam, property ownership is regulated by Sharia which is different from the capitalist system which does not limit ownership, and the socialist system which limits individual ownership. Islam with its sharia provides a concept of ownership that upholds morals and justice so that it can create economic balance in society